2021
DOI: 10.1002/glia.24107
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of arginyl‐tRNA‐protein transferase in oligodendrocytes impairs central nervous system myelination

Abstract: Addition of arginine (Arg) from tRNA can cause major alterations of structure and function of protein substrates. This post-translational modification, termed protein arginylation, is mediated by the enzyme arginyl-tRNA-protein transferase 1 (Ate1).Arginylation plays essential roles in a variety of cellular processes, including cell migration, apoptosis, and cytoskeletal organization. Ate1 is associated with neuronal functions such as neurogenesis and neurite growth. However, the role of Ate1 in glial developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Genetic experiments conducted in several tissues highlight the importance of Ate1 in mTOR-related metabolic processes, such as, cell migration, proliferation, and differentiation [ 11 , 16 , 68 , 69 ]. In this regard, we recently demonstrated that silencing Ate1 in primary oligodendrocyte cultures reduces the extent and complexity of processes during differentiation and myelination [ 19 ]. In vivo , Ate1 conditional KO in mouse oligodendrocytes leads to uncompacted myelin layers in spinal cord axons, a process regulated by the Akt/mTOR signaling in the central nervous system [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic experiments conducted in several tissues highlight the importance of Ate1 in mTOR-related metabolic processes, such as, cell migration, proliferation, and differentiation [ 11 , 16 , 68 , 69 ]. In this regard, we recently demonstrated that silencing Ate1 in primary oligodendrocyte cultures reduces the extent and complexity of processes during differentiation and myelination [ 19 ]. In vivo , Ate1 conditional KO in mouse oligodendrocytes leads to uncompacted myelin layers in spinal cord axons, a process regulated by the Akt/mTOR signaling in the central nervous system [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ate1 mediates posttranslational arginylation of a large family of proteins, including signaling and regulatory proteins, cytoskeletal components, transcription factors, endoplasmic reticulum (ER)-residing and secretory proteins, thereby affecting diverse cell biological processes and normal physiology [ 7 16 ]. Indeed, constitutive deletion of mouse Ate1 is embryonic-lethal due to defective heart development [ 17 ], whereas postnatal Ate1 ablation produces broad phenotypes, including neurological and metabolic abnormalities [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tRNA availability for protein arginylation is an additional way tRNAs may be important for OL maturation and myelination. The transfer of arginine from tRNA onto proteins, or arginylation, is a post-translational modification catalyzed by arginyl-protein-transferase 1 (Ate1) and has recently been shown to play a critical role in OL maturation ( Palandri et al, 2022 ). Various cytoskeletal regulators of OL maturation are subject to arginylation and in primary cultures of mouse OLs with a genetic ablation in Ate1, branching complexity was significantly reduced while in vivo, these mice showed fewer mature (MOG+ or MBP+) OLs, which the authors suggested could be due to impaired OL differentiation ( Palandri et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of arginine from tRNA onto proteins, or arginylation, is a post-translational modification catalyzed by arginyl-protein-transferase 1 (Ate1) and has recently been shown to play a critical role in OL maturation ( Palandri et al, 2022 ). Various cytoskeletal regulators of OL maturation are subject to arginylation and in primary cultures of mouse OLs with a genetic ablation in Ate1, branching complexity was significantly reduced while in vivo, these mice showed fewer mature (MOG+ or MBP+) OLs, which the authors suggested could be due to impaired OL differentiation ( Palandri et al, 2022 ). It is interesting to note that biallelic variants of the cytoplasmic arginine aminoacyl-tRNA synthetase ( RARS1 ) are associated with a hypomyelinating leukodystrophy ( Nafisinia et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%